ANALISIS SISTEM KERJA DROPSHIPPING MARKETPLACE TOKOPEDIA: Studi Kasus Pada Toko Hypedunk23 - Fauzan, Zulfi Muhamad; Kusmayadi, Dicki (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
This study aims to analyze the dropshipping work system on the Tokopedia marketplace and the factors that influence the decline in sales at Hypedunk23 Store. The research method uses a qualitative approach with a case study type, with data collection techniques through interviews, observation, and documentation. The results showed that the dropshipping work system at Hypedunk23 includes: (1) supplier selection based on ratings, reviews, and experience in the marketplace; (2) uploading edited product content to increase attractiveness; (3) determining prices with a margin of 10-30% of the supplier's price; (4) order processing through confirmation to the supplier and shipping on behalf of the dropshipper; and (5) handling complaints with communication and compensation. Internal factors include delays in message response due to resource constraints, stock instability, and promotions limited to marketplace features. While external factors were caused by changes in consumer trends towards sporty shoe products as well as technical constraints in Tokopedia such as slow notifications and increased administrative costs. Keywords: Dropshipping, Tokopedia Marketplace, Sales Decline, Internal and External Factors.